A geography of virtual universities in Korea - Woo-Kung Huh (Netcom)
Information and communication technologies have relaxed time-honored practices of space-time synchronization in higher education, allowing even a new type of open universities, namely virtual universities. Seventeen virtual universities and colleges have been established in Korea since 2001. This paper examined the distribution patterns of virtual universities and students, their changes over the past five years, and the patterns of class attendance. The study found that Seoul, the capital city, outweighed other regions in terms of the number of virtual universities and their students. The study also revealed local concentrations of off-line class meetings. The geography of distance education appeared to be resulted from a number of factors including the spatial structure of the nation and ruling of distance-decay.